The The Effect of Abnormal Audit Fee on Audit Quality - Heny Dewi Ratnasari (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
Abstract: This study aims to examine the effect between abnormal audit fee, which is the difference between actual audit fee and normal audit fee levels, on the audit quality proxied by accrual discretionary. The study was conducted on 414 samples of manufacturing companies listed on the Indonesia Stock Exchange for the 2013-2018 observation period. The multiple linear regression test results show a relationship between the main variables is asymmetric, which depends on the sign of abnormal audit fees. For observations with negative abnormal audit fees or below normal audit fee levels, it’s showed that there is no significant effect between audit quality and abnormal audit fees. In fact, the findings indicate that there is a negative effect between abnormal audit fees and audit quality when tested on observations with negative abnormal audit fees or above normal audit fees levels. These results indicate that there is a dependence between the auditor and the client when the client pays a high audit fee so that it is possible to let the client manage earnings through discretionary accruals, which decreases the audit quality.